Find the sum of a finite geometric sequence from n = 1 to n = 7, using the expression −4(6)^n − 1. a. 111,325 b. 526

Question

Find the sum of a finite geometric sequence from n = 1 to n = 7, using the expression −4(6)^n − 1.

a. 111,325
b. 526
c. 782
d. -22,948

in progress 0
2022-05-20T20:28:33+00:00 2 Answers 0

Answers ( 2 )

  1. Maya
    0
    2022-05-20T20:29:55+00:00

    Answer:

    -223948 is the sum of 7 terms.

    Step-by-step explanation:

    The given geometric sequence is in the form of [tex]T_{n}=-4.6^{n}-1[/tex]

    Therefore the sequence will be -25, -145, -865……..(n =7)

    Therefore sum of the seven terms = [tex]a.frac{r^{n}-1 }{(1-r)}[/tex]

    sum = [tex](-4).frac{6^{7}-1 }{6-1}=(-4).frac{(279936-1)}{(6-1)}=(-4).frac{279935}{5}=(-4).55987=-223948[/tex]

    Sum of seven terms will be = -223948

  2. Natalia
    0
    2022-05-20T20:30:10+00:00

    Now we know what the common ratio is, 6, and what the first term is, -4,
    and our nth term is 7, since we’re asked to do the sum
    from 1 to 7.
    S7= – 4(1-6(7)/(1-6))
    =-223948

Leave an answer

Browse
Browse

45:5+15*4 = ? ( )